Petroleum geology of the South Caspian Basin - Buryakovsky, Leonid A.; Chilingar, George V., 1929-; Aminzadeh, Fred. (Boston : Gulf Professional Pub., 2001)
In this information-packed volume, the authors present mathematical models and analyses for evaluating, assessing, and describing the petroleum geology of the oil-rich South Caspian Sea Basin, including eastern Azerbaijan and western Turkmenistan. Their mathematical models include descriptions of the development and structure of the surrounding geological systems and traps. Details the petrophysical properties and interrelationship with reservoir and source rocks Describes how new technology has made it possible to profitably produce off previously useless wells A valuable resource for exploration companies in the area of the South Caspian Basin.
Geology of Azerbaijan and the South Caspian Basin; Mud Volcanoes; Regional Distribution of Oil and Gas; Lithostratigraphic Framework; Onshore Oil and Gas Fields; Offshore Oil and Gas Fields.
Includes bibliographical references (p. 410-427) and indexes.
Keywords: Petroleum -- Geology -- Caspian Sea Region; Caspian Sea Region; Electronic books